Estimates of biomass and carbon in a planted forest by Schumacher & Hall method: A case study - Guerreiro, Sidnei Fonseca; Da Conceição Sartori, Anderson Antonio; Barbosa, Felipe Teles [UNESP]; Kaspary, Rosane Maria [UNESP]; Martins, Martha Santana; Marchiori, Luan Matheus (Centro Universitario de Maringa, 2021)
The planted forest may be a viable alternative for greenhouse gas mitigation. Biomass and carbon estimates contribute towards the mitigation of anthropic impacts and allow sustainable adaptation of forest management. Biomass and carbon stock above ground in a planted forest of Eucaliptus grandis between the municipalities of Borebi and Iaras in the state of São Paulo, Brazil, are estimated. The December 2016 forest inventory was used in which ages of trees were between 4 years and 2 months and 8 years, with initial planting spacing of 3.8 m x 2.1 m. Experimental area comprised six farms distributed in 141 plots, with 258 sampling points, totaling 119, 498 trees. Data set included the variables: the average height of the plant, the average diameter at height of breast, biomass of commercial volume, and equivalent carbon dioxide. The last two were estimated by allometric equations. The Schumacher & Hall regression model was used to calculate the biomass estimate, with an expansion factor of Basic Specific Mass for the genus Eucaliptus. The growth of biomass in E. grandis is calculated by Schumacher & Hall's linearized model with a 98.94% coefficient of determination, evidencing that the method may be highly useful for calculating the estimation of biomass and carbon stock in planted forests.
Estimativa de biomassa e carbono em floresta plantada adotando o modelo de Schumacher & Hall: estudo de caso
Keywords: Carbon store; Eucaliptus; Forest inventory; Schumacher & Hall